Algorithm for detecting terminal swing independent of walking speed using 6-axis sensor - Yuto IMAI; Yuta ISHII; Taku ITAMI; Jun YONEYAMA (Nihon Kikai Gakkai ronbunshu, 2023)
Walking is one of the most important activities. However, when abnormalities occur during walking, falls occur. Fractures caused by falls may significantly reduce activities of daily living and quality of life. Falls due to external factors occur during the swing phase when the leg is floating. Detection of the period from the moment the lower leg becomes vertical to the moment of the heel contact may help elucidate the phenomenon of falls in the future and may prevent falls by some manipulation during this period. Therefore, in this study, we develop an algorithm for detecting terminal swing independent of walking speed using a 6-axis sensor attached to the heel of shoes. Preliminary experiments were conducted on a treadmill at walking speeds of 2, 3, 4, and 5 km/h. The theoretical time of the terminal swing was measured using motion capture. Preliminary experimental results showed a correlation between the maximum angular velocity of the lateral direction axis of the 6-axis sensor and the acceleration in the toe direction at the beginning of the terminal swing. Therefore, this study proposes an algorithm for detecting terminal swing using the relationship between the maximum angular velocity of the lateral direction axis and the acceleration in the toe direction at the beginning of the terminal swing. Comparing the time of the beginning of the terminal swing between the proposed method and motion capture, it was confirmed that the algorithm could detect the terminal swing at walking speeds of 3, 4, and 5 km/h with a smaller error than in previous studies.